Genetic Diversity of a Novel Oil Crop, Camellia Brevistyla, revealed by ISSR DNA Markers / Mong-Huai Su, Te-Hua Hsu, Chun-Neng Wang, Kuan-Hung Lin, Ming-Chang Chiang, Ren-Dong Kang, Khiem M. Nguyen, Hoang Nguyen - Hsu, Te-Hua
Camellia brevistyla plants are used as food oil in Taiwan. To provide a method for identifying germplasm and assessing the genetic diversity of C. brevistyla, 102 individuals were collected from 29 populations in 11 counties throughout the main island of Taiwan. Inter-simple sequence repeat (ISSR) DNA markers were analyzed and a total of 176 bands were amplified. Of these, 175 bands were found to be polymorphic in these populations. Genetic similarities among populations ranged between 34.1-95.1%. Cluster analysis revealed seven groups of populations plus one outlier (C. kissii). Five individuals from two populations in the southern region were grouped into cluster V, and six populations from both regions were grouped into cluster VII. The remaining populations from the northern region were separated into different clusters from V and VII. Results of an analysis of molecular variance indicated that the variation within populations (75%) was predominantly greater than variations among counties (18%) and among regions (7%). Overall, the gene flow (Nm = 0.509) estimated from genetic differentiation (Gst = 0.534) suggested that gene flow among regions was limited. Higher genetic diversity (H = 0.317), Shannon’s index (I = 0.477), and gene flow (Nm = 0.538) of populations were found in the northern region compared to the southern region. The DNA sequences of C. brevistyla amplified by two oil-biosynthesis genes showed 99-100% homology with those of C. oleifera. Camellia brevistyla populations are highly differentiated and can serve as a basis for the food oil industry as a germplasm resource.